Tydzień obrony przeciwpożarowej. (Gdańsk : [s.n.], 1946)
Afisz z programem uroczystości, które miały miejsce w listopadzie 1946 r. w Gdańsku.
Keywords: Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- źródła